A single targeted gamma-ray irradiation induced an acute modulation of immune cells and related cytokines in EMT6 mouse-bearing tumour model - Hasan, Nurhaslina; Hasani, Narimah Abdul Hamid; Omar, Effat; Sham, Fatihah Ronny; Fuad, Syed Baharom Syed Ahmad; Abdul Karim, Muhammad Khalis; Ibahim, Mohammad Johari (IOS Press, 2023)
BACKGROUND: A complicated interplay between radiation doses, tumour microenvironment (TME), and host immune system is linked to the active participation of immune response. OBJECTIVE: The effects of single targeted 2 Gy and 8 Gy gamma-ray irradiations on the immune cell population (lymphocytes, B-cells, T-cells, neutrophils, eosinophils, and macrophages) in EMT6 mouse-bearing tumour models was investigated. METHODS: The effects of both irradiation doses in early (96 hours) and acute phase (5 to 11 days) post-irradiation on immune parameters were monitored in blood circulation and TME using flow cytometry. Simultaneously, selected cytokines related to immune cells within the TME were measured using multiplex ELISA. RESULTS: A temporary reduction in systemic total white blood count (TWBC) resulted from an early phase (96 hours) of gamma-ray irradiation at 2 Gy and 8 Gy compared to sham control group. No difference was obtained in the acute phase. Neutrophils dominated among other immune cells in TME in sham control group. Eosinophils in TME was significantly increased after 8 Gy treatment in acute phase compared to sham control (p< 0.005). Furthermore, the increment of tumour necrosis (TNF)-±, eotaxin and interleukin (IL)-7 (p< 0.05) in both treatment groups and phases were associated with anti-tumour activities within TME by gamma-ray irradiation. CONCLUSION: The temporary changes in immune cell populations within systemic circulation and TME induced by different doses of gamma-ray irradiation correlated with suppression of several pro-tumorigenic cytokines in mouse-bearing EMT6 tumour models.